2003
DOI: 10.1002/j.2168-9830.2003.tb00735.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective on Undergraduate Engineering Success for Underrepresented Minority Students

Abstract: This paper examines the various factors that contribute to the success of minority students in engineering programs by exploring past and current paradigms promoting success and analyzing models for advancing the participation of members of these populations. Included is a literature review of articles, government reports, Web sites, and archives published since 1980. Student success is correlated to several indicators, including pre‐college preparation, recruitment programs, admissions policies, financial ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
248
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(266 citation statements)
references
References 37 publications
7
248
0
Order By: Relevance
“…In doing so, there have been numerous studies conducted analyzing the student body, recruitment, retention, and attainment of minority students 4,5,6 .Such studies, however, tend to focus primarily on students of color or female students. The studies regarding faculty of color focus on the importance of faculty mentoring, pedagogical practices, and faculty development 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, there have been numerous studies conducted analyzing the student body, recruitment, retention, and attainment of minority students 4,5,6 .Such studies, however, tend to focus primarily on students of color or female students. The studies regarding faculty of color focus on the importance of faculty mentoring, pedagogical practices, and faculty development 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Work has shown that the long-term establishment of teams can lead to students continually taking the same roles and not developing additional skills 14 . Additionally, work on teaming has indicated that cognitively diverse teams produce better solutions to problems 15 ; as educators we wish to expose our students to many ways of thinking to help transform them into better problem solvers. Finally, a maximum ratio of 5 student teams per instructor/TA has been implemented in Spring 2015 to ensure the teams can be given adequate attention.…”
Section: Critical Assessment Of Implementation and Plan For Improvementmentioning
confidence: 99%
“…4 Furthermore, scholars have revealed that women and historically underrepresented racial/ethnic minorities (URMs) -Blacks, Hispanics, and Native Americans -face unique barriers (e.g., academic, social) to their success and ultimate degree completion in college, especially in science and engineering disciplines. [13][14][15][16][17][18][19][20] When comparing students' use and engagement with educational technology, differences also exist across gender. Researchers have shown that females report lower confidence, later adoption, less frequent use of educational technology such as multimedia, lower use for academic purposes, and interaction with less advanced forms of educational technology than males.…”
Section: Literature Reviewmentioning
confidence: 99%